PROSES KREATIF MEMBANGUN STRUKTUR NARATIF DALAM FILM DOKUMENTER OBSERVASIONAL œPADU AREP - Putra, I Made Denny Chrisna; Pamungkas, Epriliana Fitri Ayu; Bumiarta, Made Rai Budaya (Gorga : Jurnal Seni Rupa, 2023)
Gending rare or sekar rare in Bali represents a form of singing that parents traditionally perform for their children. The ever-expanding influence of globalization, ushering in new cultural trends that often transform into popular culture, has consistently overshadowed indigenous cultures, including that of gending rare. It is imperative to undertake preservation efforts through appropriate means before traditional cultures and artistic expressions become marginalized amidst the tidal wave of popular culture. One effective avenue for cultural preservation is the creation of observational-style documentary films. As a medium for preservation, documentary films should be meticulously crafted, not only to engage the audience but also to adhere to a coherent narrative structure. The objective of this endeavor is to unveil the creative process involved in constructing a narrative framework within the context of an observational-style documentary, titled "Padu Arep". The creation of this documentary adheres to the established five stages of film production: development, pre-production, production, post-production, and distribution. The outcomes of this undertaking demonstrate that by employing the story circle approach popularized by Dan Harmon, filmmakers can adeptly shape the narrative structure within an observational-style documentary, such as "Padu Arep". The critical analysis of interview results, subsequently interpreted in an open manner to fit seamlessly within the narrative structure, plays a pivotal role in the editing phase of this documentary. These findings are further affirmed through quality control measures during the preview editing stage, thereby affording the filmmaker the latitude to preserve their subjectivity while successfully attaining the objectives of the documentary film "Padu Arep". The implication of this research is to empower filmmakers to create observational-style documentary films without compromising the preservation of subjectivity in shaping the narrative structure.Keywords: documentary, gending rare, narrative structure. AbstrakGending rare atau sekar rare di Bali merupakan nyanyian yang dinyanyikan oleh orang tua kepada anaknya. Dampak globalisasi yang membawa budaya baru dan menjadi budaya pop selalu berhasil menghegemoni budaya lokal termasuk gending rare. Perlu melakukan pelestarian dengan cara yang tepat sebelum suatu budaya dan seni tradisi jauh tenggelam akibat marjinalisasi budaya pop. Salah satu bentuk pelestarian suatu budaya dapat berupa penciptaan film dokumenter bergaya observasional. Sebagai media pelestarian film dokumenter harus dikemas semenarik mungkin dengan memperhatikan struktur naratifnya. Tujuan penciptaan ini adalah mengungkapkan proses kreatif dalam membangun struktur naratif dalam penciptaan film dokumenter yang menerapkan pendekatan bergaya observasional di film dokumenter pendek berjudul œPadu Arep. Metode penciptaan ini menggunakan lima tahap produksi film yaitu development, pra-produksi, produksi, pasca-produksi, dan distribusi. Hasil yang didapatkan memperlihatkan bahwa dengan menggunakan pendekatan story circle yang dipopulerkan oleh Dan Harmon, sineas dapat dengan mudah membangun struktur naratif pada film dokumenter bergaya observasional berjudul œPadu Arep. Analisa terhadap hasil wawancara yang kemudian ditafsirkan secara terbuka untuk ditempatkan dalam struktur naratif menjadi proses penting dalam proses penyuntingan gambar di film dokumenter ini. Hasil ini dipertegas dengan hasil kontrol saat tahap pratinjau, sehingga pembuat film masih memiliki ruang subjektifitasnya agar tujuan film dokumenter œPadu Arep ini dapat dicapai. Implikasi penciptaan ini adalah untuk memberi ruang sineas menciptakan film dokumenter baergaya observasional tanpa kehilangan ruang subjektifitas dalam membentuk struktur naratif.Kata Kunci: dokumenter, gending rare, struktur naratif. Authors:I Made Denny Chrisna Putra : Institut Seni Indonesia DenpasarEpriliana Fitri Ayu Pamungkas : Institut Bisnis dan Teknologi IndonesiaMade Rai Budaya Bumiarta : Institut Seni Indonesia Denpasar References: Buda, I. K., Payuyasa, I. N., & P, I. M. D. C. (2020). PENDIDIKAN YANG MEMERDEKAKAN DALAM FILM œSOKOLA RIMBA. Gorga¯: Jurnal Seni Rupa, 9(2), Article 2. https://doi.org/10.24114/gr.v9i2.19823.Buda, I. K., Payuyasa, I. N., & Putra, I. M. D. C. (2018). Film Dokumenter Ã¢â‚¬Å“SesuluhÃ¢â‚¬ Sebagai Media Pembentuk Karakter Bangsa. Segara Widya¯: Jurnal Penelitian Seni, 6(2), Article 2. https://doi.org/10.31091/sw.v6i2.549.Gunawarman, R. (2021, December 18). Wawancara Narasumber Raka Gunawarman”Emoni Lestarikan Gending Rare [Teks]. https://docs.google.com/document/d/19DwVY8GwT4_44P2JsUIfcBKm5S7BBjLy/edit?usp=share_link&ouid=109642893573991947595&rtpof=true&sd=true.Ida, R. (Ed.). (2017). Budaya populer Indonesia: Diskursus Global/Lokal dalam Budaya Populer Indonesia (Cetakan Pertama). Surabaya: Airlangga University Press.Murniti, N. W. (2019). NILAI PENDIDIKAN RELEGI DALAM SEKAR RARE. Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 3(1), Article 1. https://doi.org/10.55115/widyacarya.v3i1.211.Nichols, B. (2001). Introduction to Documentary. Bloomington: Indiana University Press.Payuyasa, I. N., Susanthi, N. L., & Putra, I. B. H. K. (2022). The Embodiment of Mahakrya Lango Film. Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 5(2), Article 2. https://doi.org/10.31091/lekesan.v5i2.2157.Pertiwi, G., & Yusril, Y. (2019). PENCIPTAAN FILM FIKSI œSIRIAH JADI KARAKOK DENGAN FENOMENA LESBIAN DI SUMATERA BARAT. Gorga¯: Jurnal Seni Rupa, 8(1), Article 1. https://doi.org/10.24114/gr.v8i1.13140.Pincus, E., & Ascher, S. (2012). The Filmmaker™s Handbook: A Comprehensive Guide for the Digital Age (Fourth Edition). Plume.Wahyuni, S., Darma, S., & Saaduddin, S. (2021). PENCIPTAAN FILM FIKSI œDIBALIK SUNGAI ULAR MENGGUNAKAN ALUR NON-LINEAR. Gorga¯: Jurnal Seni Rupa, 10(1), Article 1. https://doi.org/10.24114/gr.v10i1.22018.Yasa, D. P. Y. A. T., & Payuyasa, I. N. (2019). PEMANFAATAN FILM DOKUMENTER THE COVE SEBAGAI MEDIA KAMPANYE PENYELAMATAN LUMBA. Gorga¯: Jurnal Seni Rupa, 8(2), Article 2. https://doi.org/10.24114/gr.v8i2.16072.